Data from: Phylogenomic species delimitation dramatically reduces species diversity in an Antarctic adaptive radiation - Parker, Elyse; Dornburg, Alex; Struthers, Carl; Jones, Christopher; Near, Thomas (Zenodo, 2021)
Application of genetic data to species delimitation often builds confidence in delimitations previously hypothesized using morphological, ecological, and geographic data and frequently yields recognition of previously-undescribed cryptic diversity. However, a recent critique of genomic data-based species delimitation approaches is that they have the potential to conflate population structure with species diversity, resulting in taxonomic oversplitting. The need for an integrative approach to species delimitation, in which molecular, morphological, ecological, and geographic lines of evidence are evaluated together, is becoming increasingly apparent. Here, we integrate phylogenetic, population genetic, and coalescent analyses of genome-wide sequence data with investigation of variation in multiple morphological traits to delimit species within the Antarctic barbeled plunderfishes (Artedidraconidae: Pogonophryne ). Pogonophryne currently comprises 29 valid species, most of which are distinguished solely by variation in ornamentation of the mental barbel that projects from the lower jaw, a structure previously shown to vary widely within a single species. However, our genomic and phenotypic analyses result in a dramatic reduction in the number of distinct species recognized within the clade, providing evidence to support the recognition of no more than six species. We propose to synonymize 24 of the currently recognized species with five species of Pogonophryne . We find genomic and phenotypic evidence for a new species of Pogonophryne from specimens collected in the Ross Sea. Our findings represent a rare example in which application of molecular data provides evidence of taxonomic oversplitting on the basis of morphology, clearly demonstrating the utility of an integrative species delimitation framework. : Parker_et_al2021_supplement.docx Supplementary Tables S1-11 and Supplementary Figures S1-S8. min58.phy Dataset of concatenated sequences including all loci shared across 25% (58 of 228) individuals min116.phy Dataset of concatenated sequences including all loci shared across 50% (116 of 228) individuals min174.phy Dataset of concatenated sequences including all loci shared across 75% (174 of 228) individuals noOut_min55.ustr Dataset excluding all outgroup taxa and including randomly-sampled unlinked SNPs from loci shared across 25% (55 of 218) individuals analyzed using DAPC noOut_min110.ustr Dataset excluding all outgroup taxa and including randomly-sampled unlinked SNPs from loci shared across 50% (110 of 218) individuals analyzed using DAPC noOut_min165.ustr Dataset excluding all outgroup taxa and including randomly-sampled unlinked SNPs from loci shared across 75% (165 of 218) individuals analyzed using DAPC noOut_min197.ustr Dataset excluding all outgroup taxa and including randomly-sampled unlinked SNPs from loci shared across 90% (197 of 218) individuals analyzed using DAPC noOut_min195.ustr Dataset excluding all outgroup taxa and including randomly-sampled unlinked SNPs from loci shared across 89% (195 of 218) individuals analyzed using STRUCTURE barsukovi_min61.ustr Input file for STRUCTURE including all individuals assigned to " P. barsukovi " cluster in full STRUCTURE analysis and randomly-sampled unlinked SNPs from all loci shared across 96% (61 of 63) individuals men-alb-mar_min77.ustr Input file for STRUCTURE including all individuals assigned to " P. albipinna ," " P. marmorata ," and " P. mentella " clusters in full STRUCTURE analysis and randomly-sampled unlinked SNPs from all loci shared across 89% (77 of 87) individuals mentella_min60.ustr Input file for STRUCTURE including all individuals assigned to " P. mentella " cluster in full STRUCTURE analysis and randomly-sampled unlinked SNPs from all loci shared across 94% (60 of 64) individuals scotti_min57.ustr Input file for STRUCTURE including all individuals assigned to " P. scotti " cluster in full STRUCTURE analysis and randomly-sampled unlinked SNPs from all loci shared across 96% (57 of 60) individuals min4_21tax_100loc.seqfile Input sequence file for BPP including 1-2 individuals for each of 18 traditionally-defined species of Pogonophryne and 1 putatively new species and 100 randomly-selected loci shared across all 21 individuals min4_20tax_SNAPP.phy Input data file for SNAPP divergence time analysis including 3-4 individuals for each of the 6 Pogonophryne species delimited in this study and all biallelic SNPs shared across 95% of individuals jaw_data.csv Table with all lower jaw length (LJL), head length (HL), and standard length (SL) measurements for calculation of LJL:SL and LJL:HL ratios. meristic_data.csv Table with all meristic trait data. morphometric_data.csv Table with all measured linear morphometric characters.